Isolation and genetic analysis of pure cells from forensic biological mixtures: The precision of a digital approach. (July 2017) - Fontana, F.; Rapone, C.; Bregola, G.; Aversa, R.; de Meo, A.; Signorini, G.; Sergio, M.; Ferrarini, A.; Lanzellotto, R.; Medoro, G.; Giorgini, G.; Manaresi, N.; et al.
Highlights: Homogeneous pools of cells can be isolated with DEPArray™ technology from biological mixtures. Cells obtained with DEPArray™ can be successfully genotyped using standard forensic methods. DEPArray™ system can reliably be applied to real forensic casework samples. Abstract: Latest genotyping technologies allow to achieve a reliable genetic profile for the offender identification even from extremely minute biological evidence. The ultimate challenge occurs when genetic profiles need to be retrieved from a mixture, which is composed of biological material from two or more individuals. In this case, DNA profiling will often result in a complex genetic profile, which is then subject matter for statistical analysis. In principle, when more individuals contribute to a mixture with different biological fluids, their single genetic profiles can be obtained by separating the distinct cell types (e.g. epithelial cells, blood cells, sperm), prior to genotyping. Different approaches have been investigated for this purpose, such as fluorescent-activated cell sorting (FACS) or laser capture microdissection (LCM), but currently none of these methods can guarantee the complete separation of different type of cells present in a mixture. In other fields of application, such as oncology, DEPArray™ technology, an image-based, microfluidic digital sorter, has been widely proven to enable the separation of pure cells, with single-cell precision. This study investigates the applicability of DEPArray™ technology to forensic samples analysis, focusing on the resolution of the forensic mixture problem. For the first time, we report here the development of an application-specific DEPArray™ workflow enabling the detection and recovery of pure homogeneous cell pools from simulated blood/saliva and semen/saliva mixtures, providing full genetic match with genetic profiles of corresponding donors. In addition, we assess the performance of standard forensic methods for DNA quantitation and genotyping on low-count, DEPArray™-isolated cells, showing that pure, almost complete profiles can be obtained from as few as ten haploid cells. Finally, we explore the applicability in real casework samples, demonstrating that the described approach provides complete separation of cells with outstanding precision. In all examined cases, DEPArray™ technology proves to be a groundbreaking technology for the resolution of forensic biological mixtures, through the precise isolation of pure cells for an incontrovertible attribution of the obtained genetic profiles.